Cointegration of Matched Home Purchases and Rental Price Indexes C Evidence from Singapore - Jing Li; Badi Baltagi (European Regional Science Association (ERSA), 2015)
This paper exploits the homogeneity feature of the Singapore private residential condominium market and constructs matched home purchase price and rental price series using the repeated sales method. These matched series allow us to conduct time series analysis to examine the long-term present value relationship in the housing market. Three key findings are obtained. First, we fail to establish a cointegrating relationship between the home purchase price and rental price based on nationally estimated indexes. Second, area-specific indexes demonstrate strong cross-correlations, invalidating the use of first generation panel unit root tests that ignore these cross-correlations. Third, Pesarans CIPS test indicates that the unit root hypothesis is rejected for the first difference of both indexes. We also do not reject the hypothesis that home purchases and rental price indexes are cointegrated with a cointegrating vector (1,-1).
Keywords: R00; C1; 330; Cointegration; housing market; purchase and rental price; market efficiency